Sistem Pengukuran Defleksi Crankshaft Dengan Visualisasi Pola Defleksi - Eko Supriyanto; Susilo Adi Widyanto; Sahrijal Purba; Ariyana Dwiputra Nugraha; Meiri Triani; Rasgianti Rasgianti; Ruly Sitanggang; Nur Cahyo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
The crankshaft is one of the main components of a combustion engine. Due to the engine's operating conditions and operation time, the crankshaft alignment may deviate to a particular value that should not exceed the standard limit. When the deviation value has exceeded the limit, the crankshaft will fail. In this research, the design of the crankshaft deflection measurement system was carried out with the visualization of the deflection pattern. The method is done by measuring five positions of the axial deviation between the web surfaces on each piston using a digital dial indicator. Measurement data at each point is then sent and stored in the control panel device wirelessly. Furthermore, the complete measurement data is taken, processed, and displayed in the developed software application to visually display the crankshaft deflection pattern. The test results show that the accuracy of the measuring instrument is 0.001 mm, where this value has met the prerequisites for testing the crankshaft deflection, which is 0.12 mm.